NMO Spectrum Disorders - Pfeuffer, Steffen; Strippel, Christine; Wiendl, Heinz (Neurology International Open, 2017)
Neuromyelitis optica spectrum disorders (NMOSD) represent a rare subset of chronic-inflammatory diseases of the central nervous system. Despite heterogeneities in disease activity, there is a higher degree of disability accumulation in NMOSD patients compared to MS patients. According to the revised diagnostic criteria, a recommendation was made to abandon the term NMO and to summarize these conditions as NMOSD. Clinical presentation of NMOSD patients in most cases is optic neuritis and transverse myelitis but nevertheless, NMOSD can affect most parts of the central nervous system (e. g. brainstem and hypothalamus). Originally characterized as AQP4-antibody-dependent disease, it has recently been discussed whether conditions with presence of antibodies against myelin oligodendrocyte glycoprotein (MOG) belong to the family of NMOSD. Due to the severity of the disease with often devastating relapses, systematic therapy is necessary. Usually, immunosuppressants or monoclonal antibodies with anti-inflammatory properties are used. Recently, four substances entered clinical testing for treatment of NMOSD.
Keywords: neuroimmunology; neuromyelitis optica spectrum disorder; NMOSD; myelin oligodendrocyte glycoprotein; MOG; aquaporin